1996
DOI: 10.1016/0304-3959(96)03124-7
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of transcutaneous electrical nerve stimulation upon experimentally induced delayed onset muscle soreness in humans

Abstract: The aim of the current study, for which ethical approval was obtained, was to assess the hypoalgesic efficacy of transcutaneous electrical nerve stimulation (TENS) upon acute stage (72 h) experimentally induced delayed onset muscle soreness (DOMS). TENS naive subjects (n = 48; 24 male and 24 female) were recruited, screened for relevant pathology and randomly allocated to one of four experimental groups: control, placebo, low TENS (200 microseconds; 4 Hz) or high TENS group (200 microseconds; 110 Hz). DOMS was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 6 publications
5
29
0
3
Order By: Relevance
“…Although not statistically significant, results indicated that the CLILT treatment group suffered from a slightly greater degree of pain than either the Placebo or Control groups. While perhaps surprising, these findings are in keeping with those of similar experimental studies on DOMS that used other pharmacologic and physical agents, none of which have been consistently shown to be effective for the condition [6][7][8][9][10].…”
Section: Introductionsupporting
confidence: 81%
“…Although not statistically significant, results indicated that the CLILT treatment group suffered from a slightly greater degree of pain than either the Placebo or Control groups. While perhaps surprising, these findings are in keeping with those of similar experimental studies on DOMS that used other pharmacologic and physical agents, none of which have been consistently shown to be effective for the condition [6][7][8][9][10].…”
Section: Introductionsupporting
confidence: 81%
“…TENS devices provide up to 60 times higher current levels than that seen to decrease ATP production which may explain why TENS units have not been found to be effective in treatment of DOMS (Craig et al, 1996). Typical microcurrent applications use only low and simple one channel frequencies such as 0.3 Hz, 3 Hz, 10 Hz, 30 Hz, and 300 Hz (Manley, 1994;Allen et al, 1999).…”
Section: History Of Frequency Specific Microcurrent (Fsm) Therapymentioning
confidence: 96%
“…Site of pain Low-Frequency Transcutaneous electrical nerve stimulation (TENS) Craig et al (1996) exercise does not appear more effective to accelerate recovery. This conclusion has been obtained using 30 min MHVS (high-frequency stimulations at sensory intensity) repeated eight times within 5 days after the fatiguing exercise (McLoughlin et al 2004).…”
Section: Electrical Stimulation and Recovery Of Neuromuscular Parametersmentioning
confidence: 99%
“…Conflicting results are however often reported. Craig et al (1996) compared the effectiveness of high and low-frequency TENS on subjective pain scores. Although some lower pain scores were obtained with both TENS treatments, no statistical significant effect was noticed among the conditions (high and low frequency TENS vs. placebo and control).…”
Section: Electrical Stimulation and Recovery Of Muscle Sorenessmentioning
confidence: 99%